2017
DOI: 10.1159/000479223
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Antigen 19-9-Positive Gastric Adenocarcinoma: Autopsy Findings and Review of the Literature

Abstract: Carbohydrate antigen 19-9 (CA19-9) is a well-known tumor marker for pancreatobiliary cancer, and several studies have shown that an elevated serum CA19-9 level is associated with more aggressive biological behavior in gastric cancer (GC). However, the clinicopathological characteristics of CA19-9-positive GC remain unclear. We herein report an autopsy case of CA19-9-positive GC in an 84-year-old man who was admitted to our hospital because of paralysis and anemia. Autopsy revealed an ulcerative-invasive tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Regarding the histopathological findings of CA19‐9‐positive GC, we found that CA19‐9 expression was more common in poorly differentiated adenocarcinoma rather than in tubular adenocarcinoma. While previous reports showed higher rate of CA19‐9 expression in tubular adenocarcinoma, a recent study reported no association between the histopathological subtype and CA19‐9 production . Further examination is needed to solve this issue.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding the histopathological findings of CA19‐9‐positive GC, we found that CA19‐9 expression was more common in poorly differentiated adenocarcinoma rather than in tubular adenocarcinoma. While previous reports showed higher rate of CA19‐9 expression in tubular adenocarcinoma, a recent study reported no association between the histopathological subtype and CA19‐9 production . Further examination is needed to solve this issue.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the clinical significance of CA19‐9 in GC has been reported, indicating that high serum CA19‐9 levels are associated with worse prognosis and tumor recurrence . Recently, we reported that CA19‐9‐positive GC demonstrated coagulation abnormalities, resulting in Trousseau syndrome . This phenomenon frequently occurs in pancreatic cancer, which tends to express CA19‐9.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It also plays an essential role in the intercellular adhesion of neoplastic cells, thus demonstrating a metastasis-promoting effect [ 94 , 97 ]. CA 19-9 is routinely used as a diagnostic marker in many cancers, including GC [ 98 ]. However, due to the low sensitivity and specificity of the tests, the effectiveness of this antigen in diagnosing the early stages of the disease remains limited [ 99 ].…”
Section: Potential Targets For Car-t Cell Therapymentioning
confidence: 99%
“…An elevated serum concentration of CA 19-9 occurs in 7.3–18% of GC cases and correlates with the risk of tumor relapse and poor prognosis for patients. CA 19-19 may affect tumor growth and complications in the course of GC [ 97 , 98 , 100 ]. Due to its role in the initiation and development of stomach cancer, CA 19-9 is a great potential target for personalized therapies.…”
Section: Potential Targets For Car-t Cell Therapymentioning
confidence: 99%